2004
DOI: 10.1111/j.1542-474x.2004.94580.x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and Progestin Use and the QT Interval in Postmenopausal Women

Abstract: These results suggest that unopposed estrogen in menopausal women mildly prolongs myocardial repolarization, and the effect is reversed by progesterone. Whether these findings have clinical significance requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 24 publications
3
74
0
2
Order By: Relevance
“…As regards to the increased female hormone levels during pregnancy, the risk of TdP in congenital LQTS patients is significantly decreased during pregnancy, although cardiac events are increased postpartum, suggesting the involvement of changes in serum female hormone levels (31). In post-menopausal women, although earlier studies reported conflicting findings regarding the effects of HRT on QT C interval (17), a recent study with a large study population indicated that HRT with estrogen alone causes slight but significant prolongation of the QT C interval, while the combination of HRT with estrogen and progestin consistently shortens this interval (27). Collectively, these clinical findings suggest the tempting hypothesis that the luteal hormone progesterone shortens the duration of ventricular depolarization by regulating cardiac ion channels.…”
Section: Progesteronementioning
confidence: 95%
See 3 more Smart Citations
“…As regards to the increased female hormone levels during pregnancy, the risk of TdP in congenital LQTS patients is significantly decreased during pregnancy, although cardiac events are increased postpartum, suggesting the involvement of changes in serum female hormone levels (31). In post-menopausal women, although earlier studies reported conflicting findings regarding the effects of HRT on QT C interval (17), a recent study with a large study population indicated that HRT with estrogen alone causes slight but significant prolongation of the QT C interval, while the combination of HRT with estrogen and progestin consistently shortens this interval (27). Collectively, these clinical findings suggest the tempting hypothesis that the luteal hormone progesterone shortens the duration of ventricular depolarization by regulating cardiac ion channels.…”
Section: Progesteronementioning
confidence: 95%
“…In females, there are dynamic fluctuations in QT interval and TdP risk during the menstrual cycle and pregnancy, which may correlate with changes in serum levels of ovarian steroids (3). Several studies have evaluated the potential impact of hormone replacement therapy (HRT) on QT C intervals in postmenopausal women (17,27). Although conflicting findings exist regarding HRT, these clinical findings imply that the dynamic changes in levels of female hormones have cyclical effects on action potential duration (APD).…”
Section: Gender Differences In Drug-induced Lqtsmentioning
confidence: 99%
See 2 more Smart Citations
“…In healthy premenopausal women volunteers, the susceptibility of drug-induced QT C prolongation is exaggerated in the late follicular phase where estrogen level is the highest (8). Baseline QT C in postmenopausal women who are currently taking an only estrogen-replacement therapy is slightly but significantly longer compared with the control population (9). In addition to the well-characterized influences of estrogen in cardiac repolarization concerning hormonal genomic actions (1, 10), we recently found that the physiological levels of 17β-estradiol (E2), the bioactive estrogen, acutely downregulates the hERG channel, resulting in QT C prolongation (11).…”
mentioning
confidence: 97%